2019
DOI: 10.1097/shk.0000000000001169
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Saline Solution Reduces Microcirculatory Dysfunction and Inflammation in a Rat Model of Brain Death

Abstract: HSS may improve the density of mesenteric perfused small vessels due to its effects on eNOS and endothelin-1 protein expression, and reduces inflammation by decreasing leukocyte adhesion and migration in a rat model of BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…It has been well documented that BD induces hypoperfusion in the mesenteric microcirculation, which is correlated to the reduction in the level of serum corticosterone in male rats [14,16]. Correia et al (2019) [16] described that microcirculatory hypoperfusion after BD is reduced by hypertonic saline infusion, by increase in the levels of eNOS and endothelin‐1 expression, which play key roles in the inflammatory process in vascular wall and vessel tone regulator. Estrogens exert increased bioavailability of nitrous oxide (NO) in the vascular system through nongenomic pathway, once estradiol binds to estrogen receptor‐α, leading to eNOS (endothelial isozyme) phosphorylation/activation [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that BD induces hypoperfusion in the mesenteric microcirculation, which is correlated to the reduction in the level of serum corticosterone in male rats [14,16]. Correia et al (2019) [16] described that microcirculatory hypoperfusion after BD is reduced by hypertonic saline infusion, by increase in the levels of eNOS and endothelin‐1 expression, which play key roles in the inflammatory process in vascular wall and vessel tone regulator. Estrogens exert increased bioavailability of nitrous oxide (NO) in the vascular system through nongenomic pathway, once estradiol binds to estrogen receptor‐α, leading to eNOS (endothelial isozyme) phosphorylation/activation [17].…”
Section: Discussionmentioning
confidence: 99%
“…B, Likewise, the VEGF protein expression (red) in the GFAP-positive TNC1 astrocytes (green) was obviously increased at 24 h in the OGD group compared with that in the control group; however, its expression was decreased in the HS group compared with those in the corresponding groups. 33,34,[37][38][39][40] An animal experiment found that HS may ameliorate the brain edema and brain injury induced by traumatic brain injury by reducing TNF-ɑ-and IL-1β-mediated pro-inflammatory activation. 25,31 In this study, the in vitro and in vivo results show that HS can reduce the activation of the NLRP3 inflammasome and its adaptor protein apoptosis-associated speck-like protein (ASC) in microglia.…”
Section: F I G U R Ementioning
confidence: 99%
“…This study has some limitations. We used an investigation time of 3 h, which is usually the standard time for microcirculatory studies in this model [10,12]. However, the coagulation phenomenon is installed immediately after BD induction and the perfusion compromise is maintained [11].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, to identify mechanisms involved in the microcirculatory perfusion compromise after BD, we focused on vascular elements such as NO and endothelin. We showed that after BD, increase in eNOS expression can enhance mesenteric microvascular perfusion [10] and that females present higher eNOS protein expression, despite the reduction in estradiol triggered by BD, sustaining NO synthesis and controlling vascular tone [12]. BD male animals did not show significant reduction in eNOS in the mesentery [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation